Impact of ice aggregate parameters on microwave and sub-millimetre scattering properties. (February 2019) - Ekelund, Robin; Eriksson, Patrick
Highlights: Large amount of ice aggregates generated through stochastic aggregation simulation. Extinction and back-scattering shown to follow particle effective density. Bulk scattering properties more closely related to snowfall than ice water content. 664 GHz extinction found to be relatively insensitive to particle structure. Calculated triple frequency signatures in agreement with literature. Abstract: Microwave scattering properties for 1101 aggregates were calculated using DDA (Discrete Dipole Approximation), at three typical radar bands (13.4, 35.6, 94.1 GHz) and three passive microwave frequencies (183.31, 325.15 and 664 GHz). The aggregates were generated in a semi-physical stochastic fashion and are composed of hexagonal crystals of varying axis ratio, ranging from 1/15 (plates) to 15 (columns). Horizontally aligned particles were assumed and scattering properties were assessed for zenith/nadir observations. Crystal axis ratio, number of crystals, effective density and aerodynamic area, were found to correlate with extinction and back-scattering efficiencies. However, the dependency between these variables and scattering properties vary between the frequencies. Interestingly, bulk extinction was found to have a relatively low sensitivity to particle shape at 664 GHz. Furthermore, extinction was found to be less shape sensitive than back-scattering. These results are promising for the sake of the upcoming Ice Cloud Imager (ICI) mission. In addition, for the considered set of aggregates, it is shown that both bulk extinction and back-scattering are more directly related to snow fall than ice water content. Triple frequency signatures were also calculated, which demonstrated clear dependence on constituent crystal axis ratio and conversely on aggregate effective density, in agreement with the literature.